2016
DOI: 10.1007/s12028-016-0251-0
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Fever and Neurological Outcome after Cardiac Arrest: A Retrospective Clinical Study

Abstract: Fever is frequent after CA, and Tmax in ICU is associated with worsened neurological outcome. This association becomes stronger as the timing of Tmax extends further from the CA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
8
0
2
Order By: Relevance
“…induction of hypothermia at 32À36 C) is also called rebound hyperthermia and is associated with worse outcomes, in particular with high temperatures. 211,212 Whether fever contributes to poor neurological outcome or is just a marker of severe brain injury remains unknown. To date, no randomised trial has compared controlled normothermia (i.e.…”
Section: Treatment Of Fevermentioning
confidence: 99%
“…induction of hypothermia at 32À36 C) is also called rebound hyperthermia and is associated with worse outcomes, in particular with high temperatures. 211,212 Whether fever contributes to poor neurological outcome or is just a marker of severe brain injury remains unknown. To date, no randomised trial has compared controlled normothermia (i.e.…”
Section: Treatment Of Fevermentioning
confidence: 99%
“…Fever following TTM (i.e. induction of hypothermia at 32-36 °C) is also called rebound hyperthermia and is associated with worse outcomes, in particular with high temperatures [211,212]. Whether fever contributes to poor neurological outcome or is just a marker of severe brain injury remains unknown.…”
Section: Treatment Of Fevermentioning
confidence: 99%
“…Recent small and highly biased studies have suggested that a slow and controlled rewarming rate is feasible and may be associated with better long-term neurological outcomes [30,31]. Finally, because many studies have suggested a detrimental effect of post-TTM fever on outcome [32,33], careful control of body temperature for at least 48 h following the end of rewarming is mandatory; this strategy could be titrated to patient condition (i.e., shorter if immediate awakening or prolonged in case of signs of moderate to severe cerebral insult).…”
Section: Duration Of the Rewarming Phasementioning
confidence: 99%